Silver Nanomaterials for Wound Dressing Applications - Priya Dharshini Krishnan; Dominik Banas; Ramya Devi Durai; Daniil Kabanov; Bozena Hosnedlova; Marta Kepinska; Carlos Fernandez; Branislav Ruttkay-Nedecky; Hoai Viet Nguyen; Awais Farid; Jiri Sochor; Vedha Hari B. Narayanan; et al. (MDPI AG, 2020)
Silver nanoparticles (AgNPs) have recently become very attractive for the scientific community due to their broad spectrum of applications in the biomedical field. The main advantages of AgNPs include a simple method of synthesis, a simple way to change their morphology and high surface area to volume ratio. Much research has been carried out over the years to evaluate their possible effectivity against microbial organisms. The most important factors which influence the effectivity of AgNPs against microorganisms are the method of their preparation and the type of application. When incorporated into fabric wound dressings and other textiles, AgNPs have shown significant antibacterial activity against both Gram-positive and Gram-negative bacteria and inhibited biofilm formation. In this review, the different routes of synthesizing AgNPs with controlled size and geometry including chemical, green, irradiation and thermal synthesis, as well as the different types of application of AgNPs for wound dressings such as membrane immobilization, topical application, preparation of nanofibers and hydrogels, and the mechanism behind their antimicrobial activity, have been discussed elaborately.